13. 14 + 3 {34 - 18 - 14} = 3 [6 x 2 + 17 - (2 x 7)]
Answers
Answered by
0
Answer:
I think this is ur answer...
Attachments:
![](https://hi-static.z-dn.net/files/d1b/a8718769a423dbcfc09487cc4486aef6.jpg)
Answered by
2
= 14+3{34-18-14}÷3[6×2+17-(2×7)]
=14+3{16-14}÷3[6×2+17-(2×7)]
= 14+3{2}÷3[6×2+17-(2×7)]
=14+3{2}÷3[6×2+17-(14)]
=14+3{2}÷3[12+17-(14)]
=14+3{2}÷3[29-14)]
=14+3{2}÷3[15]
=14+6÷3[15]
=14+2[15]
=14+30
=44
Similar questions
Math,
5 months ago
Social Sciences,
5 months ago
Math,
5 months ago
English,
10 months ago
Political Science,
10 months ago
Social Sciences,
1 year ago
English,
1 year ago